2016
DOI: 10.1073/pnas.1617951114
|View full text |Cite|
|
Sign up to set email alerts
|

Arginine substitution of a cysteine in transmembrane helix M8 converts Na + ,K + -ATPase to an electroneutral pump similar to H + ,K + -ATPase

Abstract: Na+,K+-ATPase and H+,K+-ATPase are electrogenic and nonelectrogenic ion pumps, respectively. The underlying structural basis for this difference has not been established, and it has not been revealed how the H+,K+-ATPase avoids binding of Na+ at the site corresponding to the Na+-specific site of the Na+,K+-ATPase (site III). In this study, we addressed these questions by using site-directed mutagenesis in combination with enzymatic, transport, and electrophysiological functional measurements. Replacement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…The mean parameters rendered from the fits to the individual experiments averaged in Fig. 8 D were V 1/2 = −38 ± 1 mV and slope factor kT/ez q = 32 ± 1 mV ( n = 7) for wild type, and V 1/2 = −109 ± 2 mV; kT/ez q = 54 ± 1 mV ( n = 6) for G99R, consistent with the mutant having an approximately eightfold decrease in overall Na + o apparent affinity; a 25-mV shift of the V 1/2 corresponds to a twofold change in external Na + o concentration ( Holmgren et al, 2000 ; Holmgren and Rakowski, 2006 ) or twofold change in overall external Na + affinity ( Li et al, 2005 ; Yaragatupalli et al, 2009 ; Meier et al, 2010 ; Vedovato and Gadsby, 2010 ; Holm et al, 2017 ).…”
Section: Resultssupporting
confidence: 56%
“…The mean parameters rendered from the fits to the individual experiments averaged in Fig. 8 D were V 1/2 = −38 ± 1 mV and slope factor kT/ez q = 32 ± 1 mV ( n = 7) for wild type, and V 1/2 = −109 ± 2 mV; kT/ez q = 54 ± 1 mV ( n = 6) for G99R, consistent with the mutant having an approximately eightfold decrease in overall Na + o apparent affinity; a 25-mV shift of the V 1/2 corresponds to a twofold change in external Na + o concentration ( Holmgren et al, 2000 ; Holmgren and Rakowski, 2006 ) or twofold change in overall external Na + affinity ( Li et al, 2005 ; Yaragatupalli et al, 2009 ; Meier et al, 2010 ; Vedovato and Gadsby, 2010 ; Holm et al, 2017 ).…”
Section: Resultssupporting
confidence: 56%
“…Similarly, Holm et al. ( 38 ) and Nielsen et al. ( 39 ) showed that changes in apparent affinity for external Na + estimated by biochemical data are comparable with those obtained by electrophysiological methods.…”
Section: Main Textsupporting
confidence: 52%
“…1 ), which replaces a serine in the Na + , K + -ATPase 2 . A cysteine to arginine mutation in TM8 of the normally electrogenic Na + , K + -ATPase converts it to an electroneutral pump like HKA 14 , highlighting the importance of a positively charged residue in the binding site of HKA. K791 along with E820 are regarded as crucial to proton transfer and the selective K + binding in the E 2 P state of the HKA.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike alkali cations, protons have to either piggyback on water molecules or will bind to the acidic amino acids thus “protonating” specific amino acids in the cation binding pocket. Such proton redistribution in the cation binding site of the closely related Na + , K + -ATPase has been extensively studied recently 8 , 14 , 23 28 because conformation-dependant protonation and deprotonation of acidic residues is deemed important for the release of Na + from the E 2 P.3Na + state, and is proposed to be critical in imparting cation selectivity (Na + versus K + ) to the Na + , K + -ATPase.…”
Section: Introductionmentioning
confidence: 99%